GUAVIRA: DIVERSIDADE DE ACESSOS POR MEIO DA CARACTERIZAÇÃO BIOMÉTRICA DOS FRUTOS - ROSA, Artur Guerra; SILVA, Mariele Trindade; MARTINS, João Pedro Godoy; FREITAS, Guilherme Jornada de; PEREIRA, Marceli Fernandes; SILVA, Adriana de Castro Correia da (ANAIS DO ENIC, 2018)
-